A systematic review of the feather mite genus Hyperpedalloptes Dubinin (Acariformes: Alloptidae) from Old World ibises (Pelecaniformes: Threskiornithidae), with descriptions of previously unknown adult morphs - Hernandes, Fabio A. [UNESP]; Mironov, Sergey V. (Systematic & Applied Acarology Soc London, Natural History Museum, 2017)
Hyperpedalloptes Dubinin (Analgoidea: Alloptidae) is one of the most amazing feather mite genera due to the strong hypertrophy of legs I in males, displayed asymmetrically in some species. Each of the three known species occurs on a particular ibis species of the genus Threskiornis (Pelecaniformes: Threskiornithidae). Based on examination of type and additionally collected materials, we (re) describe previously known and newly found male morphs of Hyperpedalloptes species and describe for the first time a female of H. petazophorus (Trouessart). We found that H. titanopedes Dubinin has three discrete morphs of males; those with asymmetrically hypertrophied legs I are considered to be heteromorphs, while males with symmetrically hypertrophied legs I and males without leg hypertrophy correspond to mesomorphs and homeomorphs, respectively. The previously known morphs of H. petazophorus and H. corymbophorus (Trouessart & Neumann) with symmetrically hypertrophied legs I are treated here as mesomorphic males.
Keywords: asymmetry; heteromorphism; polymorphism; systematics; Analgoidea